Content Validity of Reading Subject Final Exam of English Educational Study Program' Fifth Semester At Universitas Prima Indonesia (UNPRI) in Academic Year 2021/2022 - Manik, Kresna Ningsih (The Eastasouth Journal of Learning and Educations, 2023)
A qualified final test is a test containing validity. Validity refers to the extent to which a test measures what it claims to measure. It is essential that the final test content aligns with the learning objectives and the knowledge covered throughout the course. The study takes place in University Prima Indonesia (UNPRI) at the fifth semester of English Education Study Program. This study implements descriptive qualitative research by using final tests of Reading Subject which is available on spada/sistem pembelajaran dalam jaringan (online platform). The researcher took all questions which is 15 questions and syllabus of the Reading Subject to analyze the test items. Then, the researcher retyped the data and compared it with the syllabus. After that, the researcher analyzed the test items one by one and come to the percentage of the conformity and unconformity of the test items to know the quality of the content validity of the test items. From the test items’ analysis, it is concluded that 3 (29.04%) from the total question items is 15 (100%) question (no. 4, 6, 10 &11) are not appropriate to the basic competence of the syllabus whereas 12 questions namely questions number 1, 2, 3, 5, 7, 8, 9, 12, 13, 14, 15 (79.2%) are appropriate to the basic competence of the syllabus. Finally, it can be concluded that the test items of Final Test of Reading Subject are valid. A way to make a high content validity in a test can be done in some ways such as constructing and selecting items based on standard competence, basic competence, learning objectives that have been formulated in the syllabus. The lecturers must be sure that test items in the final examination of Reading should include all material and all basic competences in one semester, if it is found that there are some materials that are not included/covered in the final test, it is expected that the lecturer must give the students additional test that can cover all materials that is not included/covered in the prior test.